Development of an MRI-visible nonviral vector for siRNA delivery targeting gastric cancer - Chen Y (Dove Medical Press, 2012)
Yinting Chen1, Weiwei Wang2, Guoda Lian1, Chenchen Qian1, Lingyun Wang1, Linjuan Zeng1, Chengde Liao3, Biling Liang4, Bing Huang5, Kaihong Huang1, Xintao Shuai21Department of Gastroenterology, The Second Affiliated Hospital of Sun Yat-sen University, Guangzhou, 2Center of Biomedical Engineering, School of Chemistry and Chemical Engineering, Sun Yat-sen University, Guangzhou, 3Department of Radiology, The Third Affiliated Hospital of Kunming Medical University, Kunming, 4Department of Radiology, The Second Affiliated Hospital of Sun Yat-sen University, Guangzhou, 5Center of Animal Research, Zhongshan Ophthalmic Center Hospital of Sun Yat-sen University, Guangzhou, ChinaAbstract: An antibody-directed nonviral vector, polyethylene glycol-grafted polyethylenimine functionalized with superparamagnetic iron oxide nanoparticles and a gastric cancer-associated CD44v6 single-chain variable fragment (scFvCD44v6,-PEG-g-PEI-SPION), was constructed as a gastric cancer-targeting and magnetic resonance imaging (MRI)-visible nanocarrier for small interfering RNA (siRNA) delivery. Biophysical characterization of PEG-g-PEI-SPION and scFvCD44v6-PEG-g-PEI-SPION was carried out, including siRNA condensation capacity, cell viability, and transfection efficiency. Both the targeting and nontargeting nanocarriers were effective for transferring siRNA in vitro. The cellular uptake and distribution of nanoparticles complexed with siRNA was analyzed by fluorescence imaging and immunofluorescent staining. Moreover, the gastric cancer-targeting effect was verified in vivo by MRI and histology analysis. These results indicate that scFvCD44v6-PEG-g-PEI-SPION is a promising nonviral vector for gastric cancer gene therapy and diagnosis.Keywords: tumor targeting, CD44 variant 6, nonviral vector, small interfering RNA, magnetic resonance imaging